2018
DOI: 10.4218/etrij.2017-0131
|View full text |Cite
|
Sign up to set email alerts
|

Discrete bacterial foraging optimization for resource allocation in macrocell-femtocell networks

Abstract: Femtocells are good examples of the ultimate networking technology, offering enhanced indoor coverage and higher data rate. However, the dense deployment of femto base stations (FBSs) and the exploitation of subcarrier reuse between macrocell base stations and FBSs result in significant co‐tier and cross‐tier interference, thus degrading system performance. Therefore, appropriate resource allocations are required to mitigate the interference. This paper proposes a discrete bacterial foraging optimization (DBFO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…For exploring the designed attributes, the upcoming cognitive cellular system assists in developing regular policies which help to eliminate the production of dangerous interference from the wireless network which communicates with one another and safeguard several users. Stated that, Femtocells exploited unfilled macro cell radio resources using a game-theoretical radio resource control [2]. This model attains independent cross-tier as well as intra-tier interference reductions, however, channel detection establishes an overhead as data transmission and receiving tasks could not be processed with a limited sensing frame.…”
Section: Introductionmentioning
confidence: 99%
“…For exploring the designed attributes, the upcoming cognitive cellular system assists in developing regular policies which help to eliminate the production of dangerous interference from the wireless network which communicates with one another and safeguard several users. Stated that, Femtocells exploited unfilled macro cell radio resources using a game-theoretical radio resource control [2]. This model attains independent cross-tier as well as intra-tier interference reductions, however, channel detection establishes an overhead as data transmission and receiving tasks could not be processed with a limited sensing frame.…”
Section: Introductionmentioning
confidence: 99%
“…In the fresh food e-commerce supply chain composed of fresh food e-commerce platform and suppliers, the improvement of effort level needs to pay the corresponding effort cost, which leads to the increase of the total cost of the supply chain [17][18][19]. Wang Lei et al used wholesale price contract to help member enterprises improve the level of fresh-keeping efforts when they studied the limited capacity of fresh-keeping service of individual member enterprises in fresh agricultural products supply chain; Sana studied the effect of promotion efforts on supply chain channel coordination under uncertain market demand, and the conclusion showed that the market demand was affected by both promotion efforts and random variables, and the effect of promotion effort was not infinite increasing; Cachon et al pointed out that revenue sharing contract could encourage member enterprises to make decisions in the direction of maximizing the total profit of the supply chain; Ma et al studied the service effort problem of two-level supply chain, and concluded that only when cost sharing contract was considered in the contract could supply chain achieve perfect coordination.…”
Section: Introductionmentioning
confidence: 99%